SULPHIDE MINERALIZATION FROM EPTADENDRO AND RACHI AREAS IN EASTERN RHODOPE - Χατζηκύρκου Α.; Μιχαηλίδης Κ. (Bulletin of the Geological Society of Greece, 2004)
The sulphide mineralization from Eptadendro and Rachi areas hosted in the Upper Tectonic Unit of eastern Rhodope is studied. This mineralization is related to a fault zone of NE-SW direction. The orebodies are found along the contacts between granitoid intrusions and meta-ultrabasicbasic rocks as well as within the meta-ultrabasic-basic rocks. The ore mineral assemblages consist of pyrite and chalcopyrite as main minerals, minor sphalerite, galena, magnetite and hematite which form also local concentrations, and traces of Bi-, Ag-, and Co - Ni- minerals. Chlorite, quartz, calcite and sericite are the main gangue minerals. Folding of thin mineralized layers, brittle or ductile deformation, annealing or porphyroblasting of pyrite are typical metamorphic features confirming that mineralization has been affected by a series of metamorphic and deformation events. Pyrite porphyroblasts display a characteristic chemical zonation with higher Ni and Co contents at the marginal zones. A two-stage mineralization process was accepted for the studied area. Firstly, a stratabound mineralization hosted in the ultrabasic-basic rocks was formed in a submarine environment. Later on the intrusion of granitoids remobilized a part of this mineralization into the fault zone. Besides, the magmatic fluids of the granitoids offered new amounts of metals mainly of Zn and Pb.